Efficacy of topical agents in the background therapy of atopic dermatitis in children - E. I. Danilova; O. Yu. Trusova; V. V. Sumenko (Медицинский совет, 2018)
Atopic dermatitis (AtD) is a chronic inflammatory skin disease with complex etiopathogenesis, which begins in childhood. Purpose of the study: To evaluate the clinical efficacy and safety of Skin-cap cream as a topical background therapy in children with diabetes. Materials and methods: The study included 77 children aged 1 to 11 years with moderately severe AtD with a widespread lesion of the skin (33,5%), skin itching, inflammatory skin reaction and exacerbations occurring 3 to 4 times a year. During the study, two arms of children were formed: the treatment arm - 39 children with an average course of the disease (SCORAD index = 33,9 ± 2,2 points), who received the background therapy with the prescription of Skin-cap cream. Comparison arm: 38 children (SCORAD index = 34,2 ± 2,1 points), who received Afloderm cream as a background therapy. Results: Patients of the treatment arm showed a significant dynamics of relief of AtD symptoms as compared with the comparison arm. the differences in the duration of dermal manifestations were as follows: in the treatment arm, the time of reducing hyperaemia was 4,4 ± 1,2 days, in the comparison arm, hyperaemia was reduced at 5,7 ± 1,5 days (p< 0.05), the mean duration of alleviation of the skin itching was 3,0 ± 0,9 days and 5,8 ± 1,4 days (p< 0,05) at 6,8 and 7,3 days in the treatment arm and the comparison arm, respectively. Conclusions: The conducted study confirmed the high efficacy of the use of Skin-cap cream as a topical agent for background therapy of AtD, as compared to topical glucocorticosteroids.